Acute canopy deficits in global cities exposed by the 3-30-300 benchmark for urban nature - Thami Croeser; Roshan Sharma; Wolfgang W. Weisser; Sarah A. Bekessy (Nature Communications)
Abstract The 3-30-300 rule is a recently proposed metric that sets minimum standards for access to nature in cities for human wellbeing. It specifies that homes, schools and workplaces should have a view of 3 trees, be in a neighbourhood with over 30% tree canopy cover and be within 300 m walk of a park. This metric is an important progression for assessing urban nature because it is easy to understand, highly local, and sets a pass/fail benchmark for green infrastructure. Using datasets of over 2.5 million buildings in eight cities, we show that most buildings fail the 3-30-300 rule due to inadequate tree canopy, even in well-known global cities (the cities are Amsterdam, Buenos Aires, Seattle, Denver, New York, Singapore, Melbourne and Sydney). The ‘3’ standard was met more often, while achievement of the ‘300’ standard was patchy. Further analysis indicates that existing trees are too small for adequate canopy cover. Cities should invest in improving planting conditions to support tree growth and enhance governance to reduce premature removals and excessive pruning.